Using the Size Strain Plot Method to Specity Lattice Parameters - Jalil, Marwah T.; Harbbi, Khalid H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
X-ray diffractometers deliver the best quality diffraction data while being easy to use and adaptable to various applications. When X-ray photons strike electrons in materials, the incident photons scatter in a direction different from the incident beam; if the scattered beams do not change in wavelength, this is known as elastic scattering, which causes amplitude and intensity diffraction, leading to constructive interference. When the incident beam gives some of its energy to the electrons, the scattered beam’s wavelength differs from the incident beam’s wavelength, causing inelastic scattering, which leads to destructive interference and zero-intensity diffraction. In this study, The modified size-strain plot method was used to examine the pattern of x-ray diffraction lines (101),(121),(202),(042), and (242) for calcium titanate(CaTiO3) nanoparticles in this study. To calculate the new variables, the size strain plot method was created., X-ray line analysis and calculation of crystal size and lattice tension of calcium titanate oxide nanoparticles. It is used to calculate the crystal volume (44.7 nm) and to calculate the determination of network parameters such as the texture modulus (Tc), macro stress (MS), specific surface area (SSA), and dislocation density(η), respectively.